A model of overconfidence - Bruce A. Weinberg (Institute for the Study of Labor (IZA), 2009)
People use information about their ability to choose tasks. If more challenging tasks provide more accurate information about ability, people who care about and who are risk averse over their perception of their own ability will choose tasks that are not sufficiently challenging. Overestimation of ability raises utility by deluding people into believing that they are more able than they are in fact. Moderate overestimation of ability and overestimation of the precision of initial information leads people to choose tasks that raise expected output, however extreme overconfidence leads people to undertake tasks that are excessively challenging. Consistent with our results, psychologists have found that moderate overconfidence is both pervasive and advantageous and that people maintain such beliefs by underweighting new information about their ability.
urn:nbn:de:101:1-2009082174
Keywords: D03; D08; 330; Overconfidence; behavioral economics; information processing; Beschränkte Rationalität; Verhaltensökonomik; Informationsverhalten; Kognition; Theorie